2015
DOI: 10.1002/pros.23114
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of biochemical recurrence in pT3b prostate cancer after radical prostatectomy without adjuvant radiotherapy

Abstract: pT3b prostate cancer is a heterogeneous disease commonly associated with several high-risk features. Stratifying men with SVI by prognostic features (i.e., Gleason, PSA, node status, surgical margin status) and using these features to augment the CAPRA score will improve identification of those at higher risk for BCR that should be strongly considered for adjuvant XRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
3
12
1
1
Order By: Relevance
“…As prior series on SVI have been underpowered and offer conflicting recommendations on adjuvant therapy , in the present study we analysed the largest series of RP with SVI (3 279 patients) with the longest follow‐up (median follow‐up 148 months) to explore the utility of adjuvant therapies. We found that aRT was associated with improved survival with improvement in BCR (HR 0.83, P = 0.02), CSM (HR 0.69, P = 0.02) and OM (HR 0.85, P = 0.03) rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As prior series on SVI have been underpowered and offer conflicting recommendations on adjuvant therapy , in the present study we analysed the largest series of RP with SVI (3 279 patients) with the longest follow‐up (median follow‐up 148 months) to explore the utility of adjuvant therapies. We found that aRT was associated with improved survival with improvement in BCR (HR 0.83, P = 0.02), CSM (HR 0.69, P = 0.02) and OM (HR 0.85, P = 0.03) rates.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our present analysis confirmed the importance of local margin control for patients with SVI by finding that PSMs were associated with increased risk of BCR (HR 1.32, P < 0.001), CSM (HR 1.37, P = 0.007), and OM (HR 1.20, P = 0.01). Other investigators have debated the importance of margin status in SVI: with most series finding a significant impact , while another recent report found no significant association . A recent review highlights the conflicting evidence about the impact of PSMs on concrete endpoints such as metastasis and survival .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCR, biochemical recurrence; BMI, body mass index; GS, Gleason score; LNI, lymph node invasion; MRI, magnetic resonance imaging; PSA, prostate-specific antigen; PSM, positive surgical margin; RP, radical prostatectomy; SVI, seminal vesicle invasion. (2020) 10:5693 | https://doi.org/10.1038/s41598-020-62808-z www.nature.com/scientificreports www.nature.com/scientificreports/ and LNI, SVI has also been found to be independently associated with a poor prognosis [24][25][26][27] . However, the five-year BCR rates for patients with SVI were extremely variable, ranging from 8% to 68%.…”
Section: Discussionmentioning
confidence: 99%